Synthesis and in vitro evaluation of N-(Bromobut-3-en-2-yl)-7-methoxy-1,2,3,4-tetrahydroacridin-9-amine as a cholinesterase inhibitor with regard to Alzheimer's disease treatment - Korabecny, Jan; Musilek, Kamil; Holas, Ondrej; Nepovimova, Eugenie; Jun, Daniel; Zemek, Filip; Opletalova, Veronika; Patocka, Jiri; Dohnal, Vlastimil; Nachon, Florian; Hroudova, Jana; Fisar, Zdenek; et al. (Molecules (Basel, Switzerland), 2010)
A new tacrine based cholinesterase inhibitor, N-(bromobut-3-en-2-yl)-7-methoxy-1,2,3,4-tetrahydroacridin-9-amine (1), was designed and synthesized to interact with specific regions of human acetylcholinesterase and human butyrylcholinesterase. Its inhibitory ability towards cholinesterases was determined and compared to tacrine (THA) and 9-amino-7-methoxy-1,2,3,4-tetrahydroacridine (7-MEOTA). The assessment of IC50 values revealed 1 as a weak inhibitor of both tested enzymes.
Keywords: cholinesterasy; cholinesterasové inhibitory; Acridines; Drug Evaluation, Preclinical; Tacrine; takrin; Humans; preklinické hodnocení léčiv; butyrylcholinesterasa; Cholinesterases; lidé; Alzheimer Disease; Butyrylcholinesterase; Heterocyclic Compounds, 3-Ring; Alzheimerova nemoc; Cholinesterase Inhibitors; akridiny; heterocyklické sloučeniny tricyklické